Optimized-Hilbert for mobility in wireless sensor networks - Kamat, M. (Insitute of Electrical and Electronics Engineers, 2007)
In wireless sensor networks (WSNs), mobilizing sink node for data collection can minimize communication and maximize network lifetime. Several mobility algorithms have been proposed to control sink node's movement. However, they do not consider mobility for coverage area problem. Hilbert space-filling curves technique is modified to navigate mobile sink in traversing specfiic area of the sensor field. The algorithm is called optimized-Hilbert, which provides mobility pattern of a sink node in covering an ellipsoidal monitoring area during data collection for a specific mission by traversing the entire area from an entry point and finish at an exit point of square grids. The optimized-Hilbert requires less number of steps as compared to conventional Hilbert. Additionally, it is also compared with circular mobility, and result indicates the efficiency of optimized Hilbert.